2015
DOI: 10.1088/1367-2630/17/12/123018
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of magnetoelectricity in spin ice Dy2Ti2O7

Abstract: The intrinsic noncollinear spin patterns in rare-earth pyrochlore are physically interesting, due to their many emergent properties (e.g., spin-ice and monopole-type excitation). Recent works have suggested that the magnetic monopole excitation of spin-ice systems is magnetoelectric active, but this fact has rarely been confirmed via experiment. In this work, we performed a systematic experimental investigation on the magnetoelectricity of Dy 2 Ti 2 O 7 by probing the ferroelectricity, spin dynamics, and diele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In the high temperature range (300-600 K), the ZFC-FC -T curves were measured in a high vacuum state using a vibrating sample magnetometer (VSM) with the oven option. To probe the ferroelectric polarization (P) at low temperature region, the pyroelectric current method was used, and extrinsic contributions, such as the de-trapped charges, were carefully reduced to a minimal level [34][35]. The temperature-dependent polarization under magnetic field (H) was collected at a warming rate of 4 K/min with a fixed magnetic field during the whole process.…”
Section: Iiia Methodsmentioning
confidence: 99%
“…In the high temperature range (300-600 K), the ZFC-FC -T curves were measured in a high vacuum state using a vibrating sample magnetometer (VSM) with the oven option. To probe the ferroelectric polarization (P) at low temperature region, the pyroelectric current method was used, and extrinsic contributions, such as the de-trapped charges, were carefully reduced to a minimal level [34][35]. The temperature-dependent polarization under magnetic field (H) was collected at a warming rate of 4 K/min with a fixed magnetic field during the whole process.…”
Section: Iiia Methodsmentioning
confidence: 99%
“…Recently, observation of ferroelectricity in these systems has renewed interests in their theoretical and experimental studies [9][10][11]. Experimental finding suggests that HTO and DTO, spin ices have multiple ferroelectric transitions of different origin [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, in single crystal of HTO, only one transition at 28K has been observed [11]. On the other hand, in polycrystalline DTO two ferroelectric transitions at 25K and 13K have been reported [10]. It has been suggested that ferroelectric transitions at 60K (polycrystalline HTO), 28K (single crystalline HTO) and 25K…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar new additional peak (T s ) has also been observed for x = 1.8, 1.9 at higher temperature (T > 23. [44,74,75].…”
Section: Magnetization Analysismentioning
confidence: 99%